SOSIALISASI POLICY BRIEF OPTIMALISASI STRATEGI KONVERGENSI MEWUJUDKAN ZERO STUNTING DI KABUPATEN PAMEKASAN - Nugrahani, Cantika Iva; Sari, Agoesta Pralita; Christiana, Elisa; Noviandry R, Hilmah; Amin, Edy Suryadi; Rahman, Taufiqur; Iszakiyah, Nur; Syakura, Abdan; Hafidah, Lailatul (LPPM Universitas Bina Bangsa, 2025)
Stunting is not only a problem of malnutrition, but has a major impact on the quality of future human resources. To overcome this, a comprehensive approach involving various sectors is needed, one of which is a community-based convergence approach. The implementation of a community-based convergence strategy in Pamekasan Regency aims to reduce the stunting rate to achieve the Zero Stunting target. This strategy will strengthen cross-sector collaboration, actively involve the community, and pay attention to health, nutrition, sanitation and education interventions for families at risk of stunting. This strategy is in line with the Sustainability Development Goals (SDGs) target of “Zero Hunger”, namely eliminating all forms of malnutrition by 2030, Presidential Regulation No. 72 of 2021 concerning the acceleration of stunting reduction. East Java Province ranks 25th with the highest prevalence of stunting, while Pamekasan Regency has reached 6% by 2023. The achievement of reducing the prevalence of stunted children has not been evenly distributed to areas in Pamekasan Regency. Therefore, a holistic and multisectoral approach is needed, including the government, academics, industry, society and the media. Collaboration from the five parties can be optimally beneficial if all parties understand their roles and contributions in efforts to accelerate stunting reduction. That way the Zero Stunting target can be achieved. In addition, some of the policies and implementation strategies in this policy brief can be used as a basis for determining future policies.